135k views
5 votes
The one-to-one functions g and h are defined as follows.g(x) = 4x - 3h={(-6, 3), (-4, 7), (3, -8), (6, 4)Find the following

The one-to-one functions g and h are defined as follows.g(x) = 4x - 3h={(-6, 3), (-4, 7), (3, -8), (6, 4)Find-example-1
User Trevan
by
4.5k points

1 Answer

6 votes

It is given that


g(x)=4x-3

Now to find the inverse of g

Let


\begin{gathered} y=4x-3 \\ 4x=y+3 \\ x=(y+3)/(4) \end{gathered}

So


g^(-1)(x)=(x+3)/(4)

Now we know that


(g^(-1).g)(x)=\text{ x}

So


(g^(-1).g)(2)=2

And since


h(-6)=3

So


h^(-1)(3)=-6

User Nice Books
by
5.1k points